Effect of Symmetrical Exercises on Some Physical Variables and Level of Performance in Running 4 x 400 Relay Effectiveness - Shakir Abdulkareem, Hashim (JOM, 2024)
One of sporting events that received great attention and in particular istrack races and field. great progress in digital achievement of relaycompetitions, especially ran of short distances 4 x400 metersEffectiveness that activities have own physical and technicalcharacteristics that must be enjoyed by two short distances, such asspeed And distinctive strength of speed, as all physical capabilities ofhostility are developing in a balanced manner with technical aspects ofenhancing appropriate technique to reach good digital achievement. Oneof problems facing hostility in effectiveness of 4 X 400 meters iscontinuing is delivery of stick during performance of effectiveness in afull way and it is concern of all those interested in this Effectiveness,where delivery and receipt stage within box is one of important things thataffect level of performance and digital achievement of team and thusachievement is determined by speed and accuracy of delivery andreceipt stage, as well as lack of knowledge of coaches and athletes aboutpractical benefit of symmetrical training by introducing m in training. studyaims to Identify effect of use of symmetrical exercises on some specialphysical elements for purpose of developing acceleration during deliveryand receipt at hostile effects 4 x 400 meters follow performance andresearcher used experimental curriculum for research sample (19-20)year of (16) runners, represent 100% of original research community.Most important recommendations were: Considering rest periods in a waythat suits physical effort, where it is between repetition groups withintraining. Use of symmetrical exercises to develop parts of technical stagesof rest of athletics activities, as considered pillar of performance for eachevent and in a varied and interesting way, main part of training units.